INDEPENDENT PLAY: ENHANCING PAUD TEACHERS’ UNDERSTANDING THROUGH FIELD PRACTICE TRAINING IN DEVELOPING CREATIVE GAMES - Mado, Arifin; Wardana, Mahardika Darmawan Kusuma; Amrullah, Muchlasin (Journal of Social Comunity Services, 2025)
Objective: The purpose of this service activity is to provide training to PAUD teachers to develop games to enhance independent play. Method: The training method uses hands-on practice in the field. Results: The results of the training show that this training can improve PAUD teachers' understanding in providing game materials as a means to enhance children's independent play. Novelty: This training has implications for understanding children’s independent play among the community, especially parents.